(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Defining violence is one of the most common types of abuse at work in health care systems. The U.S. The Emergency Nurses Association found that workplace violence in the health service (3.8) is greater than privacy abuse, and also that the emergency room was especially susceptible. Objectives: To determine the violence against nurses in (ED)at teaching hospital in Mosul city/Iraq Method: To accomplish the study a retrospective research approach (2 years) was used. Sample study (218) nurse, (100) female, while male (118). The instrument developed by (Brislin, 1970) The questionnaire consist of (3) parts: part I includes demographic characteristics (6) variable such as (age, sex, qualification,working place, experience years and experience of ED). Part II: includes the main causes of the physical violence (eight items).Part III: include nonphysical violence (eight items). Results: The study found more than one-third of nurses was subject to physical abuse almost (37.61%), most of them exposure to nonphysical violence (73.3%). that mean the assault direction nurses in ED are widespread. Conclusion: The researcher concluded that the assault direction nurses who work in ED are widespread epically nonphysical violence, the most of the perpetrators of the assault direction the nurses in the EU are the relatives.